UTILIZATION OF ALMOND PULP AS THE MAIN INGREDIENT FOR MAKING COOKIES - Salsabila, Afsina Fauzia; Suhalim, Evelyn; Filimonovic, Gabriela Ayu; Juliana, Juliana (Jurnal Review Pendidikan dan Pengajaran, 2024)
Tourism is an industry that has undergone several changes throughout its history. Tourism is considered an enduring industry due to its ability to adapt to many transformations. Cookies are a type of snack that people like, namely cakes. Cookies made from flour usually consist of wheat flour, powdered sugar, chicken eggs, vanilla, margarine, cornstarch, baking powder and instant milk powder. Like other pastries, the texture of these cookies are crunchy and do not crumble easily. The aim of the research is to find out whether almond pulp can be processed into cookies. This type of research is product development with organoleptic testing. Testing was carried out on 3 limited panelists and 51 consumer panelists. Things will be tested using the five human senses with criteria regarding the taste, aroma, color, texture and appearance of the product. The results showed that almond pulp was acceptable in terms of color, aroma, texture and appearance. The implication of this research is that it effectively explains the manufacture of cookies with all tests providing a positive impact on cookie products. It can be concluded that almond pulp is acceptable in terms of color, aroma, texture and appearance.